Perwujudan Nilai Persatuan dalam Kearifan Lokal Kresnayana di Kabupaten Blitar - Vanny Rizky Ani; Ida Putri Rarasati; Arik Cahyani (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2026)
This study aims to analyze the manifestation of Indonesian unity values within the local wisdom of Kresnayana in Blitar Regency, particularly through the “Hasta Brata” performance. As a multicultural nation, Indonesia possesses diversity that represents both potential and challenge; therefore, strengthening unity values through various media, including local wisdom, is essential. This research adopts a qualitative approach with a phenomenological design to explore the experiences and involvement of cultural actors in the Kresnayana performance. Data were collected through in-depth interviews, documentation, and literature review using snowball sampling techniques, and were analyzed inductively through data reduction, triangulation, data display, and conclusion drawing. The findings indicate that Kresnayana, which originates from the reliefs of Penataran Temple, functions not only as a medium for cultural preservation but also as a means of educating unity values. In the “Hasta Brata” performance, the value of unity is reflected in the complementary relationship between Arjuna and Kresna; the value of togetherness is demonstrated through the cooperation between Anoman and Arjuna; the value of patriotism is evident in efforts to maintain world peace; and the value of Bhinneka Tunggal Ika is illustrated through the unity of characters from diverse backgrounds. Furthermore, the festival serves as a contextual learning medium in Pancasila and Civic Education (PPKn) and supports the strengthening of the Pancasila Student Profile. Thus, Kresnayana represents a concrete manifestation of the implementation of unity values in community life through a local cultural approach.